Hand Washing Practice and Food Insecurity are Associated With Undernutrition of Breastfeeding Mothers in Rural Ethiopia: A Cross-sectional Study - Alemneh Kabeta Daba; Kebede Abegaz; Anbissa Muleta; Beruk Berhanu Desalegn (SAGE Publishing, 2024)
Background: Breastfeeding mothers are prone to undernutrition. However, factors contributing to maternal undernutrition are not exhaustively understood. Hence, this study aimed to determine prevalence of undernutrition among breastfeeding mothers and identify associated factors. Methods: A cross-sectional study was conducted among 606 breastfeeding mothers from selected rural districts in Oromia and Sidama regional states of Ethiopia. Data were collected through an interviewer-administered questionnaire. Nutritional status was assessed using body mass index (BMI) and mid-upper-arm-circumference (MUAC). Logistic regression analysis was used to identify factors associated with maternal undernutrition. Results: One out of ten breastfeeding mothers was found undernourished as determined by BMI (12.6%) and MUAC (10.7%). Mothers who did not practice hand washing after cleaning children's bottom were 2 and 3 times more likely to be undernourished compared to their counters, as measured by BMI (AOR = 2.29, P  = .002) and MUAC (AOR = 3.03, P  < .001), respectively. Mothers living in mildly or moderately food insecure households (AOR = 2.37, P  = .019) were more than two times more likely to be undernourished as determined by MUAC. Mothers who breastfed children in the age range of 9 to 11 (AOR = 2.79, P  = .025) or 12 to 23 (AOR = 2.57, P  = .018) months were more than two and half times more likely to be undernourished as determined by BMI. Conclusions: Maternal undernutrition is a medium-level public health problem in rural districts of Oromia and Sidama regional states in Ethiopia. The lack of hand washing practice after cleaning a child's bottom, household food insecurity and higher child age increased the odds of maternal undernutrition. Mothers should prioritize and improve their nutritional care as the age of their breastfed child increases. Nutrition programs in rural districts of Ethiopia should also aim to improve personal hygiene practices and food insecurity integrated with implementation researches to evaluate program's impact on nutritional status of breastfeeding mothers.